2001
DOI: 10.1111/j.1945-5100.2001.tb01813.x
|View full text |Cite
|
Sign up to set email alerts
|

The Monahans chondrite and halite: Argon‐39/argon‐40 age, solar gases, cosmic‐ray exposure ages, and parent body regolith neutron flux and thickness

Abstract: Abstract-The Monahans H-chondrite is a regolith breccia containing light and dark phases and the first reported presence of small grains of halite. We made detailed noble gas analyses of each of these phases. The 39Ar-40Ar age of Monahans light is 4.533 & 0.006 Ma. Monahans dark and halite samples show greater amounts of diffusive loss of4oAr and the maximum ages are 4.50 and 4.33 Ga, respectively. Monahans dark phase contains significant concentrations of He, Ne and Ar implanted by the solar wind when this ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
(27 reference statements)
1
22
0
Order By: Relevance
“…However, these proportions may not be representative of the whole rock. Bogard et al (2001) Light-Colored Metamorphic Clasts-The light-colored clasts in the 1.2 kg Monahans stone range up to 1.5 em in maximum dimension and have subrounded to subangular shapes. They exhibit moderately recrystallized textures consistent with petrologic type 5; the chondrules do not contain glass, and olivine and low-Ca pyroxene compositions are relatively equilibrated.…”
Section: Petrographic Mineralogic and Geochemical Characteristics Ofmentioning
confidence: 99%
“…However, these proportions may not be representative of the whole rock. Bogard et al (2001) Light-Colored Metamorphic Clasts-The light-colored clasts in the 1.2 kg Monahans stone range up to 1.5 em in maximum dimension and have subrounded to subangular shapes. They exhibit moderately recrystallized textures consistent with petrologic type 5; the chondrules do not contain glass, and olivine and low-Ca pyroxene compositions are relatively equilibrated.…”
Section: Petrographic Mineralogic and Geochemical Characteristics Ofmentioning
confidence: 99%
“…(1) partial gas loss; (2) inappropriate production rate calculation; and (3) multiple irradiation ofItawa Bhopji; a space irradiation and a parent body irradiation, as happened in the case of Fayetteville (Wie1er et al, 1989) and Monahans meteorites (Bogard et al, 2001). Though the absolute cosmic-ray exposure ages might depend on the method adopted for calculating the production rates (e.g., Wie1er et al, 1996;Leya et al, 2000) the relative differences in cosmic-ray exposure ages for the two lithologies should remain the same.…”
Section: Cosmic-ray Exposure Agesmentioning
confidence: 99%
“…7, we compare the trapped noble gas amounts for the light and dark lithologies ofItawa Bhopji with the trend shown by the gas-rich meteorite Pesyanoe (Marti, 1969). The data for Monahans, having solar gases and also bearing halites (Bogard et al, 2001), is also shown for comparison. Though the presence of solar gases is clear from the trends in the dark lithologies, the absolute amounts (of 20Ne and 36Ar, for example) in both these meteorites are about an order of magnitude lower than in Pesyanoe.…”
Section: Dark Lithologymentioning
confidence: 99%
“…Large impact events that produce a thermal environment sufficiently hot to cause resetting of the 39 Ar-40 Ar ages should also cause pervasive loss of solar gases. Thus, in breccias that have reset Ar-Ar ages and solar gases, the solar gases must reside in the matrix grains that were not heated to high temperatures during breccia formation (Bogard, Garrison, and Masarik 2001). In contrast, breccias with reset Ar-Ar ages but little or no solar gases could be inferred either to have experienced prolonged burial and heating to relatively high temperatures at depth, or to contain grains that never resided at the regolith surface.…”
Section: Solar Cosmogenic and Radiogenic Gasesmentioning
confidence: 99%